The determinants of domestic savings in Cameroon: What role for institutions? - Abrams Mbu Enow Tagem; Desiree Sama-Lang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Domestic resource mobilization has rightly been placed at the centre of the 'financing for development' agenda across developing countries. While much is known about the importance of domestic taxes in contributing to this agenda, little is known about the potential importance of domestic savings, for which understanding its determinants is crucial. This paper fills that gap by identifying the robust determinants of domestic savings in Cameroon. We employ the autoregressive distributed lag model on annual data over the period from 1980 to 2018 to ascertain the robust determinants of two savings aggregates: private savings and gross savings. The empirical analysis shows that the determinants of private and gross savings are broadly the same: per capita income, income growth, and domestic credit to the private sector are associated with increases in both savings aggregates. The analysis also shows that institutions, specifically political corruption and rule of law, are themselves important determinants of savings. Finally, the analysis shows that the strong oil price hikes of the early 1980s had a direct positive impact on both savings aggregates as well as a positive impact through terms of trade.
Keywords: C32; E21; E44; G51; 330; domestic resource mobilization; domestic savings; institutions; private savings